AN ANALYSIS OF BULLYING OF THE ELEMENTARY SCHOOL STUDENTS - Azizah, Rofiqotul; Hawanti, Santhy; Wiarsih, Cicih (Dinamika, 2014)
Nowdays Bullying has been found within the students of elementary school. It can be in the form of mocking, beating, forcing for money, and even go to criminal domain such as pricking by lethal weapon. Kinds of bullying are not identified and adultsâ attitude or the othersâ permissive action to bullying made kids feel that the less good action was supposed to be good and even improved to other kind of more complex from of bullying. This research aimed to find out the teacherâs perception toward bullying, kinds and factors of bullying, teacherâs strategy in facing bullying, the teacherâs strategy in handling the students of bullying victim. The kind of the research was a qualitative by interview technique and observation for collecting the data. The subject of this research were the third grader students, teacher, headmaster in an elementary school an Kemranjen Sub district. The research showed that the bullying happened was direct verbal contact bullying, indirect non verbal, the direct physical contact and sexual abuse. The factors influencing the bullying were generation, family surroundings, negativetanded surrounding, the technology use, and the unwise of the bullyingneglect by teachers. The strategies used to handle the bullying students were by teacherâs and headmasterâs strictness, the cooperation of teacher and parents, building good communication between teacher and parents. The strategy done in handling to the bullying victims were the seriousness of the effect caused that can be observed and physically seen.Â Keywords: Bullying, Student, Teacher, Elementary School